Le théâtre de William Shakespeare, mine d’or pour les études de « droit et littérature » ; certes, mais en quel sens ? - François Ost (Clio@Themis, 2022)
How can current « law and literature » benefit from a study of Shakespeare’s theatrical work ? Basing himself on the examples of The Merchant of Venice and Measure for measure, the author offers two lines of analysis : a historical-legal perspective and a anthropologico-social perspective, with each view fertilizing the other. The author, inspired by Kant’s Critique of judgment, also identifies a third benefit from this literary analysis : the intuition of how judgment operates in human affairs – an inevitably singular judgment and yet a model for Universal to be built.